The First Soviet Convoy to the Mouth of the Lena - Barr, William (ARCTIC, 1982)
In 1933 the newly-formed Glavsevmorput' (Chief Administration of the Northern Sea Route) dispatched the first convoy of freighters via the Northern Sea Route to the mouth of the Lena to deliver cargoes bound for the Yakut ASSR. It consisted of three freighters and was escorted by the icebreaker Krasin. Despite heavy ice conditions in the Kara Sea two of the ships reached Tiksi, their destination, and unloaded their cargoes. The third ship, bound for Bukhta Nordvik with an oil exploration expedition, ran aground near its destination and turned back. Severe ice conditions in Proliv Vil'kitskogo forced all three ships to winter at the Ostrova Samuila. A shore station was built and a full scientific programme maintained all winter. Urvantsev, the chief scientist, took the opportunity to make a winter reconnaissance survey of the northern portion of Poluostrov Taymyr using half-tracks. The convoy was freed from the ice by the icebreaker Fedor Litke in the summer of 1934 and having completed their tasks all three ships ultimately returned safely to Arkhangel'sk.Key words: Soviet Northern Sea Route, Lena River, navigation, marine transport, icebreakers, convoys, Poluostrov Taymyr, Nordvik, oil exploration, wintering, all-terrain vehicles Mots clés: Route de la Mer du Nord soviétique, rivière Lena, navigation, transport maritime, brise-glace, convois, Poluostrov Taymyr, Nordvik, exploration pétrolifère, hivernement, véhicules tout-terrain